Grindelia squarrosa Extract and Grindelic Acid Modulate Pro-inflammatory Functions of Respiratory Epithelium and Human Macrophages - Gierlikowska, Barbara; Filipek, Agnieszka; Gierlikowski, Wojciech; Kania, Dominika; Stefańska, Joanna; Demkow, Urszula; Kiss, Anna K. (Frontiers in Pharmacology, 2021)
Aim of the study: Both nasal and bronchial epithelial cells have evolved sophisticated mechanisms involved in cellular response to bacterial infection. Recognition of pathogens by TLR receptors activate the NF-κB transcription factor, and lead to production of wide spectrum of cytokines (TNF-α, IL-1β, IL-6 and IL-8). Released by epithelium proinflammatory cytokines intensify migration of macrophages to damaged tissues and modulate their pro-inflammatory functions. Based on traditional use of G. squarrosa aerial parts we hypothesized that successful treatment of cold-related diseases may arise from modulation of the pro-inflammatory functions of respiratory epithelium and human monocytes/macrophages. The biological activity of G. squarrosa extract and grindelic acid were compared with clarithromycin and budesonide used as positive controls. Methods: The expression of surface receptors (TLR-4, IL-10) and expression of adhesive molecules (ICAM-1, VCAM-1, E-selectin) was analyzed with flow cytometry. The macrophage attachment to the epithelial cells was assessed fluorimetrically. The p65 NF-κB concentration and cytokine production was measured spectrophotometrically using enzyme-linked immunosorbent assay. Antibacterial activity was examined by the standard disc-diffusion method and serial dilution method according to CLSI guidelines. Results: G. squarrosa extract and grindelic acid had no antimicrobial effect. However, we noticed significant modulation of pro-inflammatory functions of LPS-stimulated nasal and bronchial epithelium. G. squarrosa extract treatment resulted in decrease of TLR-4 expression and p65 NF-κB concentration and inhibition of cytokines synthesis (IL-8, TNF-α, IL-1β and IL-6) in both cellular models. Additionally, G. squarrosa extract slightly modulated ICAM-1 expression affecting on attachment of macrophages to epithelium. Only G. squarrosa extract was able to stimulate the anti-inflammatory functions of macrophages by inducing TGF-β release and IL-10 receptor surface expression. Grindelic acid, identified as a dominant compound in the plant extract, modulated pro-inflammatory functions of epithelium and macrophages slightly. Conclusion: The obtained results support traditional use of Grindelia squarrosa preparations for a treatment cold-associated diseases symptoms. In our opinion, the observed biological effect of extract may be a consequence of synergistic effect of all compounds present in the extract.